2015
DOI: 10.1136/bmjopen-2015-008909
|View full text |Cite
|
Sign up to set email alerts
|

Is hypercapnia associated with poor prognosis in chronic obstructive pulmonary disease? A long-term follow-up cohort study

Abstract: ObjectivesTo assess whether hypercapnia may predict the prognosis in chronic obstructive pulmonary disease (COPD).DesignProspective cohort study comparing the survival of patients with COPD and normocapnia to those with chronic hypercapnia.SettingPatients with consecutive COPD were enrolled between 1 May 1993 and 31 October 2006 at two medical centres. Follow-up was censored on 31 October 2011.ParticipantsA total of 275 patients with stable COPD and aged 40–85 years were enrolled. Diagnosis of hypercapnia was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
38
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 31 publications
1
38
1
1
Order By: Relevance
“…Ju et al 18 observed that cor pulmonale patients had lower FEV1 and FEV1/FVC. Unlike our findings, Yang et al 19 observed that cor pulmonale was significantly higher in hypercapnic as compared to normocapnic patients. Verbitskii et al 20 reported insignificant hypoxemia in cor pulmonale, which progressed with decompensation of chronic cor pulmonale.…”
contrasting
confidence: 56%
“…Ju et al 18 observed that cor pulmonale patients had lower FEV1 and FEV1/FVC. Unlike our findings, Yang et al 19 observed that cor pulmonale was significantly higher in hypercapnic as compared to normocapnic patients. Verbitskii et al 20 reported insignificant hypoxemia in cor pulmonale, which progressed with decompensation of chronic cor pulmonale.…”
contrasting
confidence: 56%
“… 5 Previous studies have shown conflicting results regarding the influence of chronic hypercapnia on prognosis. 12 , 13 If hypercapnia is associated with bad prognosis, it would be more logical that by decreasing daytime PaCO 2 , survival would be positively influenced. In the present study, we did not find this, even not in a separate analysis of those patients with severe hypercapnia before NIV initiation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that chronic hypercapnia was an important symbol of poor prognosis in COPD patients. 28 , 29 Long-term survival analysis showed that mortality would increase by 30%–40% in 2 years if patients have both chronic respiratory failure and hypercapnia. 30 According to a long-term observation on stable COPD patients carried out by Leger et al, 31 stable COPD patients with long-term survival had a significantly lower PaCO 2 than the early death.…”
Section: Discussionmentioning
confidence: 99%